Intradermal vaccination with a Pseudomonas aeruginosa vaccine adjuvanted with a mutant bacterial ADP-ribosylating enterotoxin protects against acute pneumonia. Issue 6 (4th February 2019) - Baker, Sarah M.; Pociask, Derek; Clements, John D.; McLachlan, James B.; Morici, Lisa A.
Abstract: Respiratory infections are a leading cause of morbidity and mortality globally. This is partially due to a lack of effective vaccines and a clear understanding of how vaccination route and formulation influence protective immunity in mucosal tissues such as the lung. Pseudomonas aeruginosa is an opportunistic pathogen capable of causing acute pulmonary infections and is a leading cause of hospital-acquired and ventilator-associated pneumonia. With multidrug-resistant P. aeruginosa infections on the rise, the need for a vaccine against this pathogen is critical. Growing evidence suggests that a successful P. aeruginosa vaccine may require mucosal antibody and Th1- and Th17-type CD4 + T cells to prevent pulmonary infection. Intradermal immunization with adjuvants, such as the bacterial ADP-Ribosylating Enterotoxin Adjuvant (BARE) double mutant of E. coli heat-labile toxin (dmLT), can direct protective immune responses to mucosal tissues, including the lungs. We reasoned that intradermal immunization with P. aeruginosa outer membrane proteins (OMPs) adjuvanted with dmLT could drive neutralizing antibodies and migration of CD4 + T cells to the lungs and protect against P. aeruginosa pneumonia in a murine model. Here we show that mice immunized with OMPs and dmLT had significantly more antigen-specific IgG and Th1- and Th17-type CD4 + memory T cells in the pulmonary environment compared to control groups of mice. Furthermore, OMPs and dmLT immunized mice were significantly protected against an otherwise lethal lung infection. Protection was associated with early IFN-γ and IL-17 production in the lungs of immunized mice. These results indicate that intradermal immunization with dmLT can drive protective immunity to the lung mucosa and may be a viable vaccination strategy for a multitude of respiratory pathogens.